A 2018 Italian and Romanian Survey on Subclinical Hypothyroidism in Pregnancy - Negro, Roberto (Eur Thyroid J, 2018)
OBJECTIVES: Pregnancy induces changes in thyroid function, and thyroid dysfunction during gestation is associated with adverse outcomes. We examined the management of subclinical hypothyroidism and chronic autoimmune thyroiditis in pregnancy among Italian and Romanian endocrinologists. METHODS: Members of the Associazione Medici Endocrinologi (AME) and Romanian Society of Endocrinology (RSE) were invited to participate in a web-based survey investigating the topic. RESULTS: A total of 902 individuals participated in the survey, 759 of whom completed all sections. Among the respondents, 85.1% were aware of the 2017 American Thyroid Association guidelines about thyroid disease and pregnancy, and 82.9% declared that thyroid-stimulating hormone (TSH) screening at the beginning of pregnancy should be warranted. In a patient negative for peroxidase antibodies, 53.6% considered 2.5 mIU/L and 26.2% considered 4.0 mIU/L as the upper normal limit of TSH, and 50% would treat a patient with TSH 3.5 mIU/L with levothyroxine. About 20% did not suggest iodine supplementation. Isolated hypothyroxinemia detected in the first trimester would be treated by 40.8%. In patients undergoing ovarian stimulation, a TSH < 2.5 mIU/L would be targeted by 70%. CONCLUSIONS: Respondents globally appeared well informed about the management of thyroid autoimmunity and subclinical hypothyroidism in pregnancy. A more aggressive attitude in implementing iodine supplementation would be desirable. Most endocrinologists were convinced about an evident association between mild thyroid impairment and adverse outcomes in pregnancy, thus using a TSH value of 2.5 mIU/L as the threshold for diagnosing hypothyroidism and starting levothyroxine in pregnant women.